Electromyography in the evaluation of cervical and lumbosacral radiculopathy - Balbinot, Luciane Fachin; Garbino, José Antonio; Riberto, Marcelo (Acta Fisiátrica, 2010)
Electromyography (EMG) has been employed as a complementary method in the diagnosis of radiculopathy since 1950, contributing important information for diagnostic clarification, treatment planning and patient follow-up. This evidence based review sought references with emphasis on the recommendation, sensibility, specificity, reproducibility and limitations of the use of this test in the evaluation of cervical and lumbosacral radiculopathy. The references point to EMG as being an extremely useful test both in the screening and in the differential diagnosis in the suspicion of cervical or lumbosacral radiculopathy, as well as in the evaluation of the degree and extent of the injury, when the limitations of the technique are considered.